Karyotype profile of holarrhena antidysenterica (Roxb. Ex fleming) wall (Bangladesh Journal of Botany, 2023)
The karyomorphological features of Holarrhena antidysenterica (Roxb. ex Fleming) Wall. through the application of differential staining techniques (using orcein, CMA, and DAPI) were studied. After applying orcein staining, the interphase nuclei of this species exhibited a ‘simple chromocenter type’ with numerous small heterochromatin blocks and the prophase chromosomes were ‘interstitial type’. The karyotype analysis revealed that this species possesses diploid chromosome number of 2n = 22, with all metacentric chromosomes. The total length of the chromosome complement in the diploid set was 29.91 μm. A total of four CMA-positive bands were observed in this species whereas seven bands were found after DAPI-staining. Heteromorphicity was observed in the DAPI stained metaphase stage indicating the probable occurrences of chromosomal aberrations such as deletion and inversion. The karyotype profile of H. antidysenterica obtained from orcein and fluorescent banding was determined for the first time in Bangladesh.Bangladesh J. Bot. 52(4): 1085-1089, 2023 (December)